The Impact of the Tick Size Reduction on Liquidity: Empirical Evidence from the Jakarta Stock Exchange - Purwoto, Lukas; Tandelilin, Eduardus (Gadjah Mada International Journal of Business, 2004)
On July 3, 2000, the Jakarta Stock Exchange (JSX) reduced its tick size from Rp25.00 to Rp5.00. This study examines the impact of the tick size reduction on the JSX bid-ask spread, market depth, and trading activity. Using daily data, this study finds that the rupiah spread, percentage spread, and depth decreased significantly. All of these findings are not surprising since they are consistent with previous studies conducted in several different markets.In contrast to previous studies, this study finds that the key variable in determining the difference in performance of JSX stocks following the tick size reduction is the price of the stock. Specifically, all the trading activity measures e.g. in the number of trades, share volume, and rupiah volume, increased for low-priced stocks. Conversely, trading activity decreased for high-priced stocks. The possible explanation is that absolute tick size Rp5.00 is too small in economic terms for JSX high-priced stocks, so those decrease the investorsâ willingness to trade.